1981
DOI: 10.1530/jrf.0.0620039
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-induced secretion of a retinol-binding protein in the pig uterus

Abstract: A retinol binding protein(s) of molecular weight about 17 000 has been demonstrated in uterine secretions from pigs in the luteal phase of the oestrous cycle. This protein was induced in ovariectomized sows treated with progesterone or progesterone plus oestradiol, but not in sows given oestradiol or corn oil. The vitamin A content of secretions from progesterone-treated animals also increased relative to those in controls. The apparent Kd of the binding protein for retinol was 2.6 X 10(-6) M. The protein had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 8 publications
(15 reference statements)
7
37
1
Order By: Relevance
“…At the early stage of pregnancy, conceptus Tr secretes estrogen, which acts as a signal for the maternal recognition of pregnancy and affects expression of many uterine endometrial genes, including FGF7 [23], SPP1 [27], LPAR3 [28], and STAT1 [29]. Progesterone of ovarian origin also affects expression of many endometrial genes such as UF [30], UPTI [31], RBP [32], and FGF7 [33]. Thus, we hypothesized that these steroid hormones might also affect expression of TRPV6 in the uterine endometrium during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage of pregnancy, conceptus Tr secretes estrogen, which acts as a signal for the maternal recognition of pregnancy and affects expression of many uterine endometrial genes, including FGF7 [23], SPP1 [27], LPAR3 [28], and STAT1 [29]. Progesterone of ovarian origin also affects expression of many endometrial genes such as UF [30], UPTI [31], RBP [32], and FGF7 [33]. Thus, we hypothesized that these steroid hormones might also affect expression of TRPV6 in the uterine endometrium during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As progesterone is involved in secretory functions in the uterus (Adams et al 1981, Roberts et al 1987, Vallet et al 1998, differences in PR immunopresence could therefore be expected. Our results support this concept by showing PR differences between surface and glandular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…A stimulatory effect by progesterone on uterine protein secretion has been shown in pigs in several studies (Adams et al 1981, Roberts et al 1987, Vallet et al 1998. During pregnancy progesterone has an important role in preparations for uterine reception of the early embryos and for the maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 95%
“…Changes in levels of certain hormones, proteins and minerals in histotroph before day 12 of pregnancy (Geisert et al 1982a;Zavy et al 1984; will, therefore, be independent of changes in maternal endocrine function, suggesting that preimplantation embryos have a capacity to modify their own microenvironment before the maternal recognition of pregnancy. In this respect, hormones secreted by blastocysts could induce local changes in endometrial activity which are consistent with changes in the composition of histotroph during the first 10 days of pregnancy (Knight et al 1973;Basha et al 1980;Adams et al 1981;Geisert et al 1982a) and several groups have now reported capacities for steroid Heap et al 1981) and PG (Watson and Patek 1979;Davis et al 1983) synthesis by dispersed tissues of pig blastocysts collected after day 10 of gestation. Specific inhibition of endocrine activities of blastocysts is associated with impaired implantation, degenerative changes and early intrauterine mortality EI-Banna et al 1970;Hoffman 1978;Hurst and MacFarlane 1981).…”
Section: Introductionmentioning
confidence: 58%
“…Progesterone concentrated at the trophectoderm boundary layer could effect local stimulation of protein release by the endometrium (Knight et al 1973;Adams et al 1981), activate enzyme activities within apposed endometrial tissues (Roberts et al 1976), or induce inhibitors of plasmin or trypsin activity which may prevent degradation of macromolecules which are essential to conceptus development (Fazleabas et al 1982). Conceptus-derived progesterone might also protect embryos from maternal immune aggression (Siiteri and Stites 1982;Van Vlasselaer and Vandeputte 1984;Fujisaki et al 1985).…”
Section: Discussionmentioning
confidence: 99%